The public sphere in Muslim societies (Albany, New York)
ix, 191 sayfa
Keywords: “Challenging conventional assumptions, the contributors to this interdisciplinary volume argue that premodern Muslim societies had diverse and changing varieties of public spheres, constructed according to premises different from those of Western societies. The public sphere, conceptualized as a separate and autonomous sphere between the official and private, is used to shed new light on familiar topics in Islamic history, such as the role of the shari`a (Islamic religious law), the `ulama' (Islamic scholars), schools of law, Sufi brotherhoods, the Islamic endowment institution, and the relationship between power and culture, rulers and community, from the ninth to twentieth centuries“ --